2014
DOI: 10.1111/tpj.12642
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected roles for ancient proteins: flavone 8‐hydroxylase in sweet basil trichomes is a Rieske‐type, PAO‐family oxygenase

Abstract: SUMMARYMost elucidated hydroxylations in plant secondary metabolism are catalyzed by oxoglutarate-or cytochrome P450-dependent oxygenases. Numerous hydroxylations still evade clarification, suggesting that they might be performed by alternative enzyme types. Here, we report the identification of the flavone 8-hydroxylase (F8H) in sweet basil (Ocimum basilicum L.) trichomes as a Rieske-type oxygenase. Several features of the F8H activity in trichome protein extracts helped to differentiate it from a cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Additionally, in 2014 Berim and colleagues isolated an 8-hydroxylase from sweet basil that could convert salvigenin or crisimaritin to 8-hydroxysalvigenin or 8-hydroxycrisimaritin. This plastid-localized enzyme belongs to the protein family of Rieske-type oxygenases and is highly expressed in the trichomes of sweet basil leaves ( Berim et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in 2014 Berim and colleagues isolated an 8-hydroxylase from sweet basil that could convert salvigenin or crisimaritin to 8-hydroxysalvigenin or 8-hydroxycrisimaritin. This plastid-localized enzyme belongs to the protein family of Rieske-type oxygenases and is highly expressed in the trichomes of sweet basil leaves ( Berim et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is a logical consequence of the fact that Fd is a cofactor for electron transfer reactions toward two reductive enzymes of the MEP pathway (Seemann et al, 2006;Rekittke et al, 2013) and flavone hydroxylases (Berim et al, 2014), which are involved in the formation of the major products of mint GTs (monoterpenes and methoxylated flavones, respectively). In earlier versions of menpiGT_2015, Fd served as a substrate for FNR, which is the direction of electron flow in photosynthetic cells.…”
Section: Occurrence Of Gt-specific Fd/fnr Isoforms In Monoterpene-accmentioning
confidence: 99%
“…A recent study identified a novel RSO from Ocimum basilicum (basil) trichomes that functions as a flavone-8-hydroxylase with strong selectivity toward salvigenin ( Fig. 5B; Berim et al, 2014). Additional uncharacterized RSO homologs found in plant genomes may be proven to operate in specialized metabolism as well.…”
Section: Rieske-type Oxygenasesmentioning
confidence: 99%